Open‐source python‐OpenDSS interface for hybrid simulation of PV impact studies. Issue 12 (17th March 2017) - Hariri, Ali; Newaz, Alvi; Faruque, Md Omar
Abstract : This study introduces an open‐source Python‐OpenDSS simulation tool where the phasor simulation software OpenDSS is interfaced with an electromagnetic transient (EMT) program‐type simulation tool implemented in Python environment. The tool is designed to perform impact study of photovoltaic (PV) integration in distribution systems. It is composed of an EMT model of a grid‐tied PV system interfaced with a phasor model of the distribution network. The proposed tool provides an add‐on that expands OpenDSS capabilities in order to perform various PV impact studies that cannot be performed inherently by OpenDSS since they require detailed modelling. This study describes the methodology and theory behind the interfacing of the EMT model with OpenDSS. The tool is tested with various case studies using the IEEE 37‐bus system with multiple interconnected PV systems. The tool is validated by comparing its results with those of a full EMT model of the IEEE 37‐bus system simulated using SimPowerSystems. The results indicate that the hybrid tool offers significant advantages over single‐rate simulations that use either full phasor or full EMT simulation approach. It provides faster simulation time and less computational intensity, and the accuracy is remarkably close to the full blown, more complex and slower, EMT simulation.